Bioenergy production data from anaerobic digestion of thermally hydrolyzed organic fraction of municipal solid waste - A.S. Razavi; E. Hosseini Koupaie; A. Azizi; H. Hafez; E. Elbeshbishy (Data in Brief, 2019)
The presented dataset in this data article provides quantitative data on the production of bioenergy (biogas and biomethane) from mesophilic batch anaerobic digestion (AD) of thermally hydrolyzed organic fraction of municipal solid waste (OFMSW). The discussion and interpretation of the data are provided in another publication entitled “Hydrothermal Pretreatment of Source Separated Organics for Enhanced Solubilization and Biomethane Recovery” (Razavi et al., 2019). The data and information presented in the current data article include (1) the ratio of soluble to particulate chemical oxygen demand (COD) under different thermal hydrolysis condition, (2) the daily measured biogas and biomethane data, (3) the cumulative methane yield data in terms of mL CH4 produced per gram of volatile suspended solids (VSS) as well as feedstock added, (4) the ultimate methane yield data as well as the relative improvement in methane recovery compared to the control (non-hydrolyzed) digester, (5) the data of first-order organics biodegradation rate constants, (6) the procedure of measuring biogas composition via gas chromatography, (7) the procedure of converting the biogas/methane volume data acquired under the actual experimental condition (mesophilic temperature of 38 °C and atmospheric pressure) to the standard temperature (0 °C) and pressure (1 atm) condition, and (8) the procedure of determining the first-order kinetic rate constants.